Energy labeling for electric fans in Malaysia - Mahlia, T.M.I.; Masjuki, Haji Hassan; Taha, F.M.; Rahim, N.A.; Saidur, Rahman (Energy Policy, 2005)
To reduce energy consumption in the residential sector, Malaysia Energy Commission is considering implementing energy labels for household electrical appliances including electric fans in 2005. The purpose of the energy labels is to provide the consumers a guideline to compare the size, features, price and efficiency of the appliance. This paper discusses the energy label for electric fans in this country based on Malaysian Standards developed by a technical committee that reviewed the performance of household electrical appliances. This study includes methodology for the calculation of the energy efficiency star rating and projected energy usage, performance requirements, details of the energy label and the requirements for the valid application in Malaysia. The label also can be adopted for other household electrical appliances with only slight modifications.